2020
DOI: 10.1097/cpt.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiovascular Effects of Body Weight Support Treadmill Walking in Healthy Adults

Abstract: Purpose: Limited and conflicting evidence exists regarding the metabolic and cardiovascular responses of body weight support (BWS) treadmill training (BWSTT). The purpose of this study was to describe the metabolic (as assessed by oxygen uptake) and cardiovascular responses to varying levels of BWSTT in healthy adult subjects. Methods: Twenty-one subjects (10 females; 34.5 [6.7] yr.; 74.6 [14.3] kg; 170.8 [6.9] cm; 26.1 [5.3] kg/m2) provided their infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In contrast to the above investigations, several studies [13,14,19] have found no change in VO 2 with BWSTT. Hoffman and Donaghe [13] showed through linear regression analysis similar response to VO 2 and HR in 12 healthy subjects walking at 25% and 50% BWS.…”
Section: Subjectsmentioning
confidence: 59%
See 3 more Smart Citations
“…In contrast to the above investigations, several studies [13,14,19] have found no change in VO 2 with BWSTT. Hoffman and Donaghe [13] showed through linear regression analysis similar response to VO 2 and HR in 12 healthy subjects walking at 25% and 50% BWS.…”
Section: Subjectsmentioning
confidence: 59%
“…From this predicted value, VO 2 levels of 35% and 50% VO 2 max were calculated, and treadmill speed (maximum of 91.1 m/min) and grade values were calculated for subsequent laboratory testing [25]. These exercise intensities were selected to approximate self-selected speeds of subjects from previous investigations at this laboratory [19,20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations